In vitro evaluation of Penicillium chrysogenum Snef1216 against Meloidogyne incognita (root-knot nematode) - Aatika Sikandar (Nature Portfolio, 2020)
Abstract Root-knot nematode (Meloidogyne incognita) is chief plant parasitic nematode of various crops globally. Meanwhile, the negative side effects on human health and environmental concerns associated with haphazard uses of chemical nematicides. Hence, the search for a safe and effective approach is more relevant. The present study was aimed to evaluate the nematicidal potential of Snef1216 (Penicillium chrysogenum) against M. incognita at different concentrations (5%, 10%, 25%, 50%, 75% and 100%) and with the nutritious medium. The egg hatching inhibition and mortality of second stage juveniles of M. incognita were assessed after 6, 12, 24, 48 and 72 h exposure. Results revealed that egg hatching inhibition and percent mortality of M. incognita increased with increasing concentration and exposure time. The highest mortality of juveniles was recorded at 100% conc. i.e., 24.20%, 36%, 66%, 78% and 97.8% at 6, 12, 24, 48 and 72 h, respectively. The highest ovicidal activity was recorded at 100% concentration with 5.20% of eggs hatching. The outcome suggested that Snef1216 (P. chrysogenum) resulted in the lowest LC50 value was recorded as 3718.496 at 6 h exposure period followed by 10479.87, 11186.682, 14838.58 and 24001.430 at 72, 12, 48 and 24 h respectively via ovicidal assay. Whereas, in the larvicidal assay, the lowest LC50 value demonstrated at 72 h being 17.628% exposure period followed by 28.345, 50.490, 215.710 and 482.595% at 48, 24, 12 and 6 h respectively. It is concluded that Snef1216 has potential being used as a biocontrol agent against M. incognita and can serve as a source of a novel nematicidal agent of fungal origin.